Understanding early molecular mechanisms of abnormal myelination in neurological conditions by characterising Ermin deficiency - Oh, Sher Li (2024)
Abnormal myelination has been observed across several neurodegenerative conditions, and is hypothesised to be a key factor leading to disease pathophysiology. Here, we investigate early molecular mechanisms leading to abnormal myelination using Ermin deficiency as a model. Ermin is a gene expressed specifically in oligodendrocytes during the late stage of myelination, and its altered expression has been associated with several neurological conditions, including epilepsy, schizophrenia, and a familial form of multiple sclerosis, although its involvement in their pathophysiology is still unclear. We studied the transcriptome of Ermin-deficient mice using gene co-expression and differential gene expression analyses to investigate early transcriptional effects of Ermin deficiency across age and sex. We observed altered expression of transcription factors at early ages, and in protein processing and synaptic function over time. In silico gene perturbation and ChIP-seq analysis were used to elucidate the roles that differentially expressed transcription factors play in oligodendrocyte differentiation and as well as in their effects on protein processing and synaptic function. Finally, we assessed the relationship between early molecular changes in Ermin deficiency in neurological conditions using genome-wide association studies. Our observations suggest that there are common mechanisms between Ermin deficiency and biological processes influenced by genetic variants of genetic generalised epilepsy. Our findings demonstrate that in the Ermin-deficient model of abnormal myelination, early changes in transcription factor expression are associated with dysregulation in oligodendrocyte differentiation, synaptic organisation, and protein modification. These transcriptional changes are also enriched for genetic variants in neurological disease and provide insight into the early molecular mechanisms involving abnormal myelination in neurological disorders.